Development of Microsatellite Markers for a Dioecious Herpetospermum pedunculosum (Cucurbitaceae). (February 2020) - Chen, Zhu-Qing; Zhou, Zhi-Li; Wang, Lin-Lin; Meng, Li-Hua; Duan, Yuan-Wen
Understanding the evolution of flower diversity is a central topic in plant evolutionary ecology, and natural selection on floral traits via male fitness could be estimated quantitatively using microsatellites. Here, based on RNA sequencing, we developed simple sequence repeat primers and verified polymorphisms in 2 wild populations of Herpetospermum pedunculosum (Cucurbitaceae), a dioecious annual plants native to the Himalaya Mountains. A total of 131 paired primers were designed; 15 paired primers were found to be polymorphic, with the expected heterozygosity varying between 0.280 and 0.767. We also identified 58 genotypes in 20 plants from the 2 populations. Conclusively, these primers could be effective in examining male fitness and population genetic structure of H pedunculosum in future studies.